The right of platform workers to transparent and predictable working conditions - Gołaś, Jakub (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
The present study analyses the right of platform workers to transparent and predictable working conditions, emphasising the key importance of transparency and stability of working conditions for the protection of workers. In the context of platform work, which is characterised by significant non-transparency and unpredictability resulting, among other things, from the automation of management, it was highlighted that the lack of complete and clear information on the essential elements of employment deepens the asymmetry in the relationship between the platform worker and the digital labour platform. The analysis in this chapter explores the concept of the right to transparent and predictable working conditions, highlighting the arguments that support its recognition as a fundamental principle of labour law. The study draws upon a range of sources, with particular emphasis on EU directives 2019/1152 and 2024/2831, and their impact on the development of standards for transparent and predictable working conditions. The analysis places particular emphasis on the Platform Work Directive, whose standards, including those relating to the presumption of an employment relationship and algorithmic transparency, establish an autonomous benchmark for transparency and predictability of platform working conditions.